2015
DOI: 10.1016/j.robot.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Learning agent’s spatial configuration from sensorimotor invariants

Abstract: The design of robotic systems is largely dictated by our purely human intuition about how we perceive the world. This intuition has been proven incorrect with regard to a number of critical issues, such as visual change blindness. In order to develop truly autonomous robots, we must step away from this intuition and let robotic agents develop their own way of perceiving. The robot should start from scratch and gradually develop perceptual notions, under no prior assumptions, exclusively by looking into its sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 57 publications
1
33
0
2
Order By: Relevance
“…Note that no superscript a is needed as all receptive fields are moved together during saccades. Moreover motors could potentially be redundant regarding the sensor's displacements in the world, in which case the agent would have to discover its actual working space (see [13] for an example of such a sensorimotor structuring). The naive agents we consider have no specific policy to explore the world.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Note that no superscript a is needed as all receptive fields are moved together during saccades. Moreover motors could potentially be redundant regarding the sensor's displacements in the world, in which case the agent would have to discover its actual working space (see [13] for an example of such a sensorimotor structuring). The naive agents we consider have no specific policy to explore the world.…”
Section: Problem Formulationmentioning
confidence: 99%
“…L'utilisation des courbes noyau pour la construction d'une carte interne de l'espace a été évaluée dans (Laflaquière, O'Regan, Argentieri, Gas & Terekov, 2015) lors d'une approche purement expérimentale. Dans ces travaux, un agent redondant équipé d'un bras et d'un capteur analogue à une caméra est utilisé pour découvrir l'ensemble des courbes noyaux et obtenir une carte des configurations atteignables par son capteur.…”
Section: -Représentation Interne Via L'action Et La Perceptionunclassified
“…L'existence d'un isomorphisme entre l'espace quotient ℳ/≡ A et l'espace de travail < prouve la pertinence de son utilisation dans les travaux précédents (Laflaquière, 2013 ;Laflaquière, O'Regan, Argentieri, Gas & Terekov, 2015 ;Marcel, Garcia, Argentieri & Gas, 2015) pour la découverte de la notion d'espace. Différentes stratégies ont d'ailleurs été proposées pour sa construction dans les travaux précédents, que ce soit pour la construction d'une représentation de l'espace de travail <, ou d'une sous-partie de celui-ci (le corps de l'agent).…”
Section: Figure 10unclassified
“…Working on the agent's body was initially envisaged as a way to put the environment dependency of the representation aside. Indeed, as formalized later in this paper, the fact that the environmental state can possibly evolve along exploration has already proven to be a major theoretical difficulty [17], [21]. This paper proposes to tackle the environment dependency by generalizing the formalism initially proposed in [19].…”
Section: Introductionmentioning
confidence: 96%
“…This initial formalization led to the demonstration that an agent can, without any a priori, infer the so-called "dimension of space". Further works like [17] have also shown that, beyond the dimension of space, it is possible to build a motor internal representation of the positions occupied by the agent's end-effector without external knowledge about its working space. Despite the use of a curvilinear component analysis (CCA) [18] and the definition of adapted Hausdorff distances in the agent motor space, this work lacks a proper mathematical formalization and they are no clear definitions on the properties or spaces that are actually captured by the agent.…”
Section: Introductionmentioning
confidence: 99%